From fallow ground to common ground: Perspectives on future land uses in the San Joaquin valley under sustainable groundwater management. (1st May 2023) - Espinoza, Vicky; Bernacchi, Leigh A.; Eriksson, Max; Schiller, Anna; Hayden, Ann; Viers, Joshua H.
Abstract: Agriculture dominates California's San Joaquin Valley with over five million acres of farmland produces 400 different commodities ranging from nuts, tree fruits, vines, and row crops. During dry years agricultural production in the San Joaquin Valley uses about 53% of total applied water in the state. Implementation of California's Sustainable Groundwater Management Act (SGMA) will restrict groundwater pumping, likely reducing irrigated agricultural land use resulting in conversion to alternative land uses. To promote collaborative and inclusive efforts to repurpose agricultural land, California's legislature established a funding program administered by the Department of Conservation, the Multibenefit Land Repurposing Program (MLRP), in 2021. To ensure that land repurposing plans under the MLRP and SGMA represent San Joaquin Valley community needs this paper examines public perceptions of future land uses under SGMA through a phone survey. Respondents (n = 197) were recruited through a stratified random sample of mobile numbers registered within communities in the San Joaquin Valley classified as disadvantaged communities (DACs) (n = 32). Our results show that most respondents were somewhat (33%) or not at all (54%) familiar with SGMA, highlighting the need for outreach efforts to overcome barriers to representation, translation, and education about future water and land use decisions. Survey respondents identified secure water supplies (e.g., groundwater recharge) (35%) and less-water intensive agriculture (27%) as their top land use priorities to address groundwater overdraft under SGMA, indicating that the status quo for land use is preferred to alternative land uses. Preference for maintaining agriculture as primary land use (27%), we correlated with agricultural identity and lack of interest in community or global benefits such as schools and climate change mitigation. The findings from this study underscore the local variability in land use values and the importance to engaging local communities in land use decision-making, especially as they relate to changing current practices toward a more climate-resilient but agriculturally productive future with less land and less water. Graphical abstract: Image 1 Highlights: Most respondents were not familiar with the 2014 California Sustainable Groundwater Management Act (SGMA). Respondents showed a high level of support for groundwater recharge for economic and community well-being. Secure water supplies and less water-intensive agriculture were perceived as important land use priorities. The role of agriculture in the local economy and climate change impacts were given higher priority than other land uses. Outreach efforts need to overcome barriers to representation related to education and language to increase DAC inclusion.